Pengaruh E-Trust dan E-Service Quality terhadap Repurchase Intention melalui E-Satisfaction sebagai variabel intervening (studi pada pengguna Lazada di Kecamatan Banyumanik) - Alexandra Devaraell Susan; Naili Farida; Widayanto Widayanto (Universitas Diponegoro, 2024)
This study was conducted to determine whether there is an influence of E-Trust and E-Service Quality as independent variables on Repurchase Intention as the dependent variable through E-Satisfaction as an intervening variable. The sample taken for the study was 100 respondents with a non propability sampling technique, namely purposive sampling through the snowball effect. The data was taken using a questionnaire, literature study. This research is descriptive type with data processing using SmartPLS 3.3 software. The results showed that there is a positive and significant influence between E-Trust and E-Service Quality on Repurchase Intention through E-Satisfaction. The effect of E-Trust, E-Service Quality and E-Satisfaction on Repurchase Intention is 43.6% and the effect of E-Trust and E-Service Quality on E-Satisfaction is 53.7%. Based on this, Lazada needs to increase security by displaying SSL certificates so that trust in customers increases and improve the service system for customers. In addition, it is hoped that Lazada can provide offers in the form of promotions, discounts so that customers are more satisfied with Lazada and will make repeat purchases to LazadaKeywords: E-trust; E-Service Quality; E-Satisfaction; Repurchase IntentionPenelitian ini dilakukan guna mengetahui apakah terdapat pengaruh dari E-Trust dan E-Service Quality sebagai variabel independen terhadap Repurchase Intention sebagai variabel dependen melalui E-Satisfaction sebagai variabel intervening. Sampel yang diambil untuk penelitian sebanyak 100 responden dengan Teknik pengambilan sampel non propability sampling yakni purposive sampling melalui snowball effect. Data tersebut diambil menggunakan kuesioner, studi Pustaka. Penelitian ini bertipe deskriptif dengan pengolahan data menggunakan software SmartPLS 3.3 Hasil Penelitian menunjukan bahwa ada pengaruh positif dan signifikan antara E-Trust dan E-Service Quality terhadap Repurchase Intention melalui E-Satisfaction. Pengaruh E-Trust, E-Service Quality dan E-Satisfaction terhadap Repurchase Intention sebesar 43,6% dan pengaruh E-Trust dan E-Service Quality terhadap E-Satisfaction sebesar 53,7%. Berdasarkan hal tersebut Lazada perlu meningkatkan keamanan dengan menampilkan sertifikat SSL agar kepercayaan pada pelanggan meningkat dan meningkatkan sistem pelayanan pada pelanggan. Selain itu diharapkan Lazada dapat memberikan tawaran berupa promosi, diskon agar pelanggan lebih puas terhadap Lazada dan akan melakukan pembelian ulang terhadap Lazada.Kata Kunci: E-Trust; E-Service Quality; E-Satisfaction; Repurchase Intention